Rola nadzoru bankowego w systemie kontroli banków w zakresie metodologii adekwatności kapitałowej - Niewiadoma, Maria (The Role of Banking Supervision in the Control System of Banks in the Context of the Capital Adequacy, 2006)
The criteria of control system of banks are not a set of minimum requirements by which control is effective if each of the criteria is met. The most popular is the capital adequacy based on the Basel Committee on Banking Supervision's methods of capital's measurement with proposals for 2006, 2007 and 2008. Therefore banks must estimate the level of the banking risks, especially the credit risk, the operational risk and the capital factor (coefficient). This problem is also connected with the increasing role of the banking supervision in the development of the international commercial banks in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 9-15